Analysis for spatial-temporal changes of grain production and farmland resource: Evidence from Hubei Province, central China. (10th January 2019) - Chai, Ji; Wang, Zhanqi; Yang, Jun; Zhang, Liguo
Abstract: Grain production and farmland utilization are the key issues to the stability of a region. As China becomes increasingly industrialized and urbanized, there have been many challenges to food security and farmland protection. This study conducts a case study on Hubei Province in Central China, aiming to reveal the spatial-temporal changes and the interaction between grain production and farmland resource by spatial analysis model. And accordingly, it provides suggestion and countermeasures to achieve the goal of strictly protecting farmland resource and safeguarding food security. The gravity center of grain production moved 120.40° and 13.45 km in the northwest, while the gravity center of farmland area moved 8.14° and 5.60 km to the northeast during the entire period, which revealed that the effects of farmland area change on grain production were more obvious than the inputs of agricultural machinery and chemical fertilizers, and grain production in northern regions accounted for an increasing proportion in Hubei Province. The level of spatial mismatch of farmland resource and grain production in Hubei Province fluctuated during the study period of 2002–2014, but it was gradually remedied after 2011. The quantity of regions with mid and high sensitivity continuously increased from 10 to 25 during 2002–2014, which revealed that the change of farmland area has an increasing influence on grain production in Hubei Province. The results can provide operable recommendations for efficient use of resources, sustainable development and maintaining food security from the aspect of spatial-temporal changes. Highlights: We combined gravity center model, spatial mismatch and sensitivity analysis to reveal the spatial-temporal changes. The effects of farmland area change on grain production were more obvious than the other inputs in Hubei Province. The spatial mismatch of farmland resource and grain production in Hubei Province fluctuated during 2002 to 2014. North and Central Hubei Province were becoming more important in the regional grain production.